Prevalence of infectious and parasitic diseases in the service of patients with special needs of the Faculty of Stomatology of the Universidad Peruana Cayetano Heredia - Leyva, Hector (2023)
Objective: To determine the prevalence of medical diagnoses of infectious and/or parasitic diseases in patients who attended the Special Patients Stomatology Service (EPE) of the Cayetano Heredia Peruvian University. Material and methods: The population (n = 38) comprised the number of medical diagnoses of patients with infectious and/or parasitic diseases who attended the EPE service during 2015 and 2016. The information was transferred to a database in the Excel 2017 program to be processed and analyzed as required by the Stata 12 program. Results: Of 1718 medical diagnoses, infectious and/or parasitic diseases had a prevalence of 2.21% (n = 38). Within this group of diseases, human immunodeficiency virus (HIV) was the most prevalent, with 63.2 % (n = 24), with the male sex being the most prevalent with 79 % (n = 19). Within the age group of 21 to 40 years of age, the second most prevalent specific diagnosis was hepatitis A with 15.8 % (n = 6), whereas the female sex was the most prevalent with 83 % (n = 5). Conclusions: The specific diagnosis within the group of infectious and/or parasitic diseases with the highest prevalence was HIV, with 63.2% (n = 24).